2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591793
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary evaluation of continuous, shoe-integrated weight measurements for heart failure patients

Abstract: Weight measurements are part of current medical care for congestive heart failure (CHF) patients. In this work, we explore the potential of shoe-mounted pressure sensors to automatically and remotely estimate the weight of CHF patients. We show that weight estimation accuracy degrades due to human subject movement. Moreover, we show that for a standing human subject the accuracy is influenced by the characteristic of the sensor used to measure pressure. Our experimental evaluation of various pressure sensors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Additional implantable hemodynamic monitoring (IHM) devices are in development or in the clinical trial phase (Table 2) [34][35][36]. The Cordella System (Endotronix, Lisle, Illinois, USA) uses a hand-held reader to synchronize with the implanted PAP sensor along with recording vital signs and patientreported symptoms.…”
Section: Pressor Sensors In Developmentmentioning
confidence: 99%
“…Additional implantable hemodynamic monitoring (IHM) devices are in development or in the clinical trial phase (Table 2) [34][35][36]. The Cordella System (Endotronix, Lisle, Illinois, USA) uses a hand-held reader to synchronize with the implanted PAP sensor along with recording vital signs and patientreported symptoms.…”
Section: Pressor Sensors In Developmentmentioning
confidence: 99%
“…Adherence to regular self-weighing is variable with some studies suggesting that less than half of HF patients reported compliance with daily weight measurement [32]. Wearable biosensors that can be integrated into shoes might represent an effortless method for continuous weight monitoring in HF patients and provide the opportunity for weight-based timely intervention while patients are still at home or in the ambulatory setting [33].…”
Section: Objective Assessments: From Implantable To Wearable Devicesmentioning
confidence: 99%
“…So far, various body weight monitoring systems have developed. Some of them work using fiber optic loops [2], pressure sensor [3], weight sensor [4] and force sensor [5], the other chose to use structured light sensor [6]. Some researcher investigates particular parameter, body mass index using speech signal [7] [8].…”
Section: Introductionmentioning
confidence: 99%